Assessment of serological evidence for mumps virus infection in vaccinated children. - Dittrich, S; Hahné, S; van Lier, A; Kohl, R; Boot, H; Koopmans, M; van Binnendijk, R (2011)
It is estimated that at least one-third of mumps virus infections in non-vaccinated individuals are asymptomatic. Little information is available whether this proportion is the same among those vaccinated. We validated a commercial oral fluid mumps IgG-specific Enzyme Immunoassays (EIA) with vaccinated control groups to identify symptomatic and asymptomatic mumps virus infections in vaccinated individuals during a mumps outbreak in The Netherlands. A vaccinated control group was required to define a new cutoff value for the assay, because of the presence of low but significant levels of IgG antibodies in oral fluid as a result of mumps vaccination in the past. With a new cutoff, calculated using receiver operator characteristic analysis, we identified an attack rate of 7-10% compared to 2.7% based on clinical symptoms among vaccinated children. This finding has important implications when studying transmission patterns, strain virulence, as well as mumps vaccine effectiveness to protect from infection rather than disease.